School leadership based on islamic values at smp negeri 2 candiroto satu atap, canggal village, candiroto subdistrict - Sholeh Kurniandini; Linda Lestari; Airin Khofifah; Dian Anggrainy Kusumaningrum; Daimatul Farichah; Arifah Maulida; Zaidatul Arifah; Husna Nashihin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study aims to determine the implementation of Islamic values-based school leadership and to identify the supporting and inhibiting factors in the implementation of Islamic values in school leadership at SMP Negeri 2 Candiroto Satu Atap, Canggal Village, Candiroto District, Temanggung Regency. This research uses a qualitative approach with a field study method. Data collection techniques included observation, in-depth interviews with principals and teachers, and documentation of leadership activities and school policies. The results showed that the principal's leadership at SMP Negeri 2 Candiroto Satu Atap has implemented Islamic values such as trustworthiness, fairness, shura, and sincerity in carrying out his duties. The principal is not only an administrative manager, but also a moral and spiritual role model who encourages the creation of a harmonious, religious, and participatory school climate. Supporting factors for the implementation of Islamic values in leadership include the principal's commitment, teachers' support, and the religious culture of the surrounding community. The inhibiting factors are limited human resources, lack of infrastructure and limited access to technology. Nevertheless, the contextual and collaborative leadership approach is able to overcome these obstacles, so that Islamic values remain the main foundation in managing and developing the school.